Factors Affecting the Frequency of Visits to the Posyandu: Faktor-Faktor yang Mempengaruhi Frekuensi Kunjungan ke Posyandu - Erma, Dwi; Faisal, Elvyrah; Khatimah, Khusnul (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
Based on data from the Palu City Health Office regarding the visits of toddlers to posyandu, Mamboro is in the 3rd position with a percentage of 73.33%. This study aims to determine the factors that affect the frequency of visits to the Posyandu in West Mamboro, the working area of ​​the Mamboro Community Health Center. This type of research is analytic with a cross-sectional design. Sampling was done by taking data at the health center, with a total sampling technique. Data collection was carried out by direct interviews using a questionnaire. Data analysis used the chi-square test with a value of α = 0.05. The results showed that the frequency of active visits to posyandu was 72.4%. The percentage of unemployed and active workers at the posyandu was 58.7% (p value = 0.225;> 0.05). The percentage of good and active knowledge at the posyandu was 29.0%. The percentage of good family motivation makes mothers under five active to posyandu 62.3% (p-value = 1,000;> 0.05). The percentage of good performance of health workers makes mothers under five active to posyandu 57.9%. The percentage of good cadre performance makes mothers under five active to posyandu 56.5%. The conclusion is that there is an influence between work and the frequency of visits, there is no influence between knowledge, family motivation, the performance of health workers, and performance of cadres with the frequency of visits to posyandu.